A new record of the stromateoid fish Psenopsis intermedia (Piontrovskiy, 1987) from Indian waters - Thomas, Sujitha; Rohit, Prathibha (Indian Journal of Fisheries, 2011)
The occurrence of Psenopsis intermedia off Malpe, in the Arabian sea, which is not recorded so far from the Indian waters is reported. The comparison of the mersitic and morphometric characters of the specimens with the holotype and paratype of the species is presented